Pazopanib has equivalent anti-tumor effectiveness and lower Total costs than Sunitinib for treating metastatic or advanced renal cell carcinoma: a meta-analysis - Deng, Huan (BMC Cancer, 2019)
BACKGROUND: Sunitinib and pazopanib are extensively used as first-line treatment of metastatic renal cell carcinoma (mRCC). We performed this meta-analysis to assess the anti-tumor effectiveness, toxicity, and total costs of the two drugs among patients with mRCC/advanced RCC (aRCC). Materials and Methods: PubMed, ScienceDirect, Scopus, Web of Science, Ovid MEDLINE, the Cochrane Library, Embase, and Google Scholar were searched to obtain eligible articles. The endpoints included progression-free survival (PFS), overall survival (OS), adverse effects (AEs), and per-patient-per-month (PPPM) costs. RESULTS: We included 14 medium- to high-quality studies. Both drugs were valid for mRCC/aRCC, with equivalent PFS (hazard ratio (HR) =1.06, 95% confidence interval [CI]: 0.98–1.15, P = 0.13), OS (HR = 0.92, 95% CI: 0.79–1.07, P = 0.29), objective response rate (ORR, risk ratio (RR) =1.03, 95% CI: 0.93–1.13, p = 0.58), and disease control rate (DCR, RR = 1.03, 95% CI: 0.94–1.22, P = 0.54). Sunitinib had more dosage reductions and higher PPPM (weighted mean difference = − 1.50 thousand US dollars, 95% CI: − 2.27 to − 0.72, P = 0.0002). Furthermore, more incidences of severe fatigue, thrombocytopenia, and neutropenia were recorded for sunitinib, but pazopanib had more liver toxicity. In subgroup analysis, studies from the US reported longer OS (HR = 0.86, 95% CI: 0.77–0.95, P = 0.004) and higher ORR (RR = 1.24, 95% CI: 1.03–1.51, P = 0.03). CONCLUSIONS: Pazopanib provides equivalent anti-tumor effectiveness and lower PPPM as compared with sunitinib for mRCC/aRCC. Great care should be given to pazopanib-treated patients with abnormal liver function. Nevertheless, more large-scale, high-quality studies are required. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s12885-019-5704-3) contains supplementary material, which is available to authorized users.